2021
DOI: 10.3390/su132111997
|View full text |Cite
|
Sign up to set email alerts
|

An Agile System to Enhance Productivity through a Modified Value Stream Mapping Approach in Industry 4.0: A Novel Approach

Abstract: Worldwide, industries are emphasizing the development of an agile system to sustain higher productivity, which can be applied to ensure improvements in all production conditions in industry 4.0. In the present scenario, several methods are used for improvements in production, such as value stream mapping, kaizen, just in time, Kanban, and total productive maintenance, etc., The objective of the present research article is to produce an agile system to sustain improvements in productivity through a methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…e results showed that smart manufacturing-related information and digital technologies were costly for most small and medium enterprises and significantly influenced by the imposition from the environment. Tripathi et al [53] developed an agile system to improve operational performance using a methodology coupled with VSM. e developed method was validated by improving the operating performance of a production management system in Industry 4.0 environment.…”
Section: Notable Contributions Of Lean and Smartmentioning
confidence: 99%
“…e results showed that smart manufacturing-related information and digital technologies were costly for most small and medium enterprises and significantly influenced by the imposition from the environment. Tripathi et al [53] developed an agile system to improve operational performance using a methodology coupled with VSM. e developed method was validated by improving the operating performance of a production management system in Industry 4.0 environment.…”
Section: Notable Contributions Of Lean and Smartmentioning
confidence: 99%
“…Industries around the world are under immense pressure on the issue of improving production performance in the present scenario. Therefore, the industry is emphasizing the development of a sustainable method that can eliminate the negative effects present in the industry and can improve every condition of the production system [6,8,11,15,22,29,35,36]. Developing such a method is a challenge for the people of the industry.…”
Section: Future Research Directionmentioning
confidence: 99%
“…Mewujudkan proses bisnis yang memenuhi tujuan klien dalam hal kualitas, kecepatan, dan biaya ialah salah satu tujuan utama VSM (Tripathi et al, 2021). Namun, dalam operasional bisnis yang sebenarnya, banyak tantangan praktis yang muncul sebagai akibat dari rutinitas yang diikuti oleh para pelaku UMKM ketika melakukan kegiatan produksi (Boonsthonsatit & Jungthawan, 2015).…”
Section: Metode Pelaksanaanunclassified